Preparation of Carbon Molecular Sieve for Pressure Swing Adsorption Concentrating Low-Concentration Methane - Li, Jiaming; Li, Guangxue; Jiang, Feng; Bu, Jia; Zhao, Mingzhu; Zhan, Hualu; Chu, Yang (Asian Journal of Chemistry, 2012)
In this paper, the samples of carbon molecular sieves were prepared by phenolic resin. The used technology of XRD, IR, SEM, BET to characterize surface properties and microstructure of carbon molecular sieves and used ZC36 high resistance meter to determine the surface and volume resistance of carbon molecular sieves. Study the influence of carbonization temperature, carbonization time, chemical vapour deposition time and chemical vapour deposition temperature on products. The results show that the carbon molecular sieves have the properties of high selective adsorption and adsorption capacity on the condition of carbonization temperature at 850 ºC, carbonization time in 2.5 h, chemical vapour deposition time in 2 h and chemical vapour deposition temperature at 700 ºC. XRD analysis shows: The microstructure of carbon molecular sieves is graphite layer type structure formed by amorphous carbon. The IR analysis shows that there are a small number of oxygen functional groups on the surface of carbon molecular sieves. SEM analysis shows that the surface pore basic shape of carbon molecular sieves is the narrow slit structure. BET analysis shows that the average of pore size of carbon molecular sieves is 2.3 nm. ZC36 high resistance meter determined result shows that the carbon molecular sieves we prepared belong to the static electricity conductor.